On a general partial integral equation of Barbashin type - B.G. Pachpatte
The aim of the present paperis to study some basic qualitative properties of solutions of a general partial integral equation of Barbashin type which occur frequently in applications. a variant of a certain integral inequality with explicit estimate is obtained and used to establish the results.
Keywords: Partial integral equation; Barbashin type; Discrete analogues